SISI POSITIF SUPORTER SEPAKBOLA SEBAGAI KONSUMEN OLAHRAGA - Eka Wahyudhi, Andi Sultan Brilin Susandi; Nasrullah, Ahmad; Nugroho, Sigit (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Football supporters are the lifeblood of a club, because fans can be an income source for a club. The behavior of football fans is greatly influenced by the atmosphere of the match and the safety of all parties involved. Apart from being supporters of a club, supporters can also be consumers of sports, especially football. The presence of supporters can increase the club's income by buying tickets, club marcindace, and becoming television consumers. Supporters can make the atmosphere of the game more interesting by their presence in the stadium, because it can burn the enthusiasm of football players. The other side of the presence of supporters as consumers is to unite differences between ethnicities and cultures, high solidarity between supporters, helping to popularize football through television and social media platforms, helping to maintain the health of spectators and interacting socially with fellow football fans.